2015
DOI: 10.1111/een.12286
|View full text |Cite
|
Sign up to set email alerts
|

Elevated anthocyanins protect young Eucalyptus leaves from high irradiance but also indicate foliar nutritional quality to visually attuned psyllids

Abstract: Elevated anthocyanins protect young Eucalyptus leaves from high irradiance but also indicate foliar nutritional quality to visually attuned psyllids Abstract. 1. Foliar colour changes with age and, as a consequence, reflects the internal physiology of leaves. Anthocyanins are 'red' pigments known for their photoprotective role in young leaves and have been suggested to influence the host-finding behaviour of insect herbivores. The existence of colour vision in some species of Eucalyptus-feeding psyllid provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Hence, it is possible that sensory modalities other than olfaction may play a more important role in the location of juvenile leaves by C. eucalypti . In addition, Eucalyptus -feeding psyllids, including the four species used in this study, have been shown to exploit visual cues such as leaf color and size to locate host leaves of the preferred age [15,16,17]. As a result, compelling evidence suggests that vision plays a predominant role in host location by these psyllids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is possible that sensory modalities other than olfaction may play a more important role in the location of juvenile leaves by C. eucalypti . In addition, Eucalyptus -feeding psyllids, including the four species used in this study, have been shown to exploit visual cues such as leaf color and size to locate host leaves of the preferred age [15,16,17]. As a result, compelling evidence suggests that vision plays a predominant role in host location by these psyllids.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory, mechanical and/or gustatory cues perceived during selection determine whether the insect “settles” and initiates sustained feeding and oviposition (acceptance) or whether it re-engages in host finding (rejection). Visual cues such as leaf shape, size and color or even light polarization have been identified as important factors in host finding by some psyllids [15,16,17,18,19,20]. The significance of plant-specific and presumably more reliable olfactory cues provided by HPVs remains uncertain [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, phenological synchrony with host plants, especially in the case of host alternation, is key for the long-term fitness of psyllids. Reported examples of such synchrony, manifested through colour preference change of psyllids in parallel with host phenology, are that of C. pyricola ( Krysan and Horton 1991 , Horton and Lewis 1997 , Cooper et al 2012 ) and three Eucalyptus -feeding psyllids ( Farnier and Steinbauer 2016 ). Our results showed that, after flowering (immigration period), the effectiveness of the white colour decreased to the level of yellow traps.…”
Section: Discussionmentioning
confidence: 99%
“…The psyllids involved here presumably had arrived later, no longer directly from conifers, but from neighbouring hedges or they were immigrants having dwelled in the orchard itself for a few weeks. The phenologically synchronised colour preference may also confer a selective advantage to C. pruni over competitors, akin to the case of Eucalyptus -feeding psyllids ( Farnier et al 2014 , Farnier and Steinbauer 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glycaspis psyllids prefer soft, young leaves presumably due to their superior nutritional quality (Farnier and Steinbauer 2016; Moore 1961; Steinbauer et al 2015). Hence, lerps tend to occur on crown or regenerating foliage and are often abundant in the year following a fire (Beveridge 1883; Yen 2015).…”
Section: Cultural Significance Of Lerps For Aboriginal Australiansmentioning
confidence: 99%